Phosphorylation of S6RP in peritubular capillaries of kidney grafts and circulating HLA donor-specific antibodies - Raïch-Regué, Dalia; Gimeno, Javier; Llinàs-Mallol, Laura; Menéndez, Silvia; Benito, David; Redondo, Dolores; Pérez-Sáez, M. José; Riera, Marta; Reed, Elaine F.; Pascual, Julio; Crespo, Marta (Frontiers in Medicine, 2022)
Antibody-mediated rejection (ABMR) caused by donor-specific HLA-antibodies (DSA) is a mediator of allograft loss after kidney transplantation (KT). DSA can activate microvascular endothelium damage through the mTOR pathway. In this study we assessed the mTOR pathway activation by DSA in KT with ABMR (ABMR+DSA+) compared to controls (ABMR-DSA-), biopsies with ABMR changes without DSA (ABMR+DSA-) and DSA without ABMR changes (ABMR-DSA+), and the potential modulation by mTOR inhibitors (mTORi). We evaluated 97 biopsies: 31 ABMR+DSA+, 33 controls ABMR-DSA-, 16 ABMR+DSA- and 17 ABMR-DSA+ cases. Regarding immunosuppression of full ABMR+DSA+ and controls, 21 biopsies were performed under mTORi treatment (11 of them ABMR+DSA+ cases) and 43 without mTORi (20 of them ABMR+DSA+) so as to explore its effect on the mTOR pathway. Biopsies were stained for C4d, Ki67 and phosphorylated (p) S6RP, ERK and mTOR by immunohistochemistry. Labelling was graded according to peritubular capillary staining. ABMR biopsies showed significantly higher C4d, p-S6RP and Ki67 staining in peritubular capillaries (ptc) compared to controls, and light differences in p-ERK or p-mTOR. mTORi treatment did not modify p-S6RP, p-mTOR and p-ERK staining. Diffuse p-S6RP in ptc in the biopsies significantly associated with circulating HLA-DSA independently of graft rejection, and with worse death-censored graft survival. These findings suggest that activation of endothelium through the mTOR pathway evidence different mechanisms of damage in ABMR+DSA+ and ABMR+DSA- despite similar histological injury.